Efeito dos níveis dietéticos de metionina e lipídios no desempenho zootécnico de juvenis do Litopenaeus vannamei cultivados em salinidade isosmótica e hiperosmótica - Mejia, Edras Rodimiro Rodriguez (2022)
The present study evaluated the effect of dietary levels of methionine (Met) and lipids on the growth performance of juvenile Litopenaeus vannamei reared under isosmotic and hyperosmotic salinities. Six practical diets were prepared containing three levels of total Met (7, 8 and 9 g kg-1, as-fed basis) each with two lipid levels (60 and 75 g kg-1, as-fed). Each diet set was evaluated under isosmotic (21-25 g L-1) and hyperosmotic (43-48 g L-1) salinities. A total of six to seven tanks were assigned to each diet and salinity, totaling 80 tanks of 0.5 m3, kept under a roofed area with continuous water recirculation and aeration. Shrimp with an average weight of 2.98 ± 0.28 g (n = 4,560) were stocked at 100 animals m-2(57 shrimp tank-1) and fed for 56 days. At harvest, water salinity reached an average of 23.0 ± 1 g L-1 for the isosmotic (n = 1,440) and 45.0 ± 0.9 g L-1 for the hyperosmotic conditions (n = 1,440). Final shrimp survival ranged from a minimum of 67.5 ± 3.65% to a maximum of 100%. Final survival was affected by salinity concentration, but no influence from the diets was detected. The hyperosmotic condition favored a higher survival compared to lower salinity. No influence of dietary Met level and (or) the lipid content on gained shrimp yield was detected. However, a lower yield was recorded under 23 g L-1(between 581 ± 99 and 666 ± 65 g m-2) compared to the 45 g L-1 (between 804 ± 75 and 818 ± 34 g m-2). Final shrimp body weight (BW) was influenced by water salinity, dietary Met and lipid levels. There was also a significant interaction between these parameters. Under the hyperosmotic condition, shrimp achieved a lower BW compared to those farmed under an isosmotic salinity. Under a salinity of 23 g L-1, a higher BW was observed when shrimp were fed diets containing 60 g kg-1 lipids compared to 75 g kg-1, regardless of the dietary Met levels. Under these conditions, when shrimp were fed 60 g kg-1 lipids, shrimp BW was maximized with 9 g kg-1 Met. Under the hyperosmotic condition, BW was maximized with 8 g kg-1 of Met with the same lipid content. In conclusion, L. vannamei can maximize its growth performance under a hyperosmotic salinity with diets containing a lower dietary Met content compared to isosmotic salinity. Within the investigated salinity ranges, an increase in dietary lipid content, from 60 to 75 g kg-1, was either deleterious or did not promote an increase in shrimp growth performance, regardless of the dietary Met level.